Quality control of 5mg diazepam suppositories manipulated in the city of Campos Goytacazes – RJ - Canzian, Renata Aparecida Venturi (2012)
Diazepam suppositories are widely used by children and elderly, and require close attention to quality control because it is a controlled prescription drug. The objective of the study was to analyze diazepam suppositories manipulated in Campos dos Goytacazes, RJ, to verify if they are within the required quality standards, and offer safety and efficiency to patients. We analyzed samples of 5mg diazepam suppositories acquired in five randomly selected pharmacies, identified as Pharmacy A, Pharmacy B, Pharmacy C, Pharmacy D, and Pharmacy E. We ran tests on average weight, organoleptic control, hardness, melting point, and dissolution. Data was analyzed and compared with the requirements of the Brazilian Pharmacopoeia. This analysis was made over a table in Excel. We conclude that only C Pharmacy was approved in all tests, and this is the only laboratory that has analyzed the quality of the product warranty. Laboratories A, B, D and E have been approved in some tests, and failed one or more tests. To ensure quality control, suppositories needed to pass in all tests, which was not the case of these labs. Therefore, we recommended the following procedures to the investigated laboratories: changes in packaging, greater precision in handling, quality control prior to dispensing the product, and efficient pharmaceutical care service.